MicroRNA-143 targets ERK5 in granulopoiesis and predicts outcome of patients with acute myeloid leukemia - Hartmann, Jens-Uwe; Müller-Tidow, Carsten (Cell death & disease, 2018)
Hematopoiesis, the formation of blood cells from hematopoietic stem cells (HSC), is a highly regulated process. Since the discovery of microRNAs (miRNAs), several studies have shown their significant role in the regulation of the hematopoietic system. Impaired expression of miRNAs leads to disrupted cellular pathways and in particular causes loss of hematopoietic ability. Here, we report a previously unrecognized function of miR-143 in granulopoiesis. Hematopoietic cells undergoing granulocytic differentiation exhibited increased miR-143 expression. Overexpression or ablation of miR-143 expression resulted in accelerated granulocytic differentiation or block of differentiation, respectively. The absence of miR-143 in mice resulted in a reduced number of mature granulocytes in blood and bone marrow. Additionally, we observed an association of high miR-143 expression levels with a higher probability of survival in two different cohorts of patients with acute myeloid leukemia (AML). Overexpression of miR-143 in AML cells impaired cell growth, partially induced differentiation, and caused apoptosis. Argonaute2-RNA-Immunoprecipitation assay revealed ERK5, a member of the MAPK-family, as a target of miR-143 in myeloid cells. Further, we observed an inverse correlation of miR-143 and ERK5 in primary AML patient samples, and in CD34+ HSPCs undergoing granulocytic differentiation and we confirmed functional relevance of ERK5 in myeloid cells. In conclusion, our data describe miR-143 as a relevant factor in granulocyte differentiation, whose expression may be useful as a prognostic and therapeutic factor in AML therapy.
Gesehen am 26.11.2024